Mutants of Escherichia coli "cryptic" for certain periplasmic enzymes: evidence for an alteration of the outer membrane. - Beacham, I R (1977)
Mutants in which the expression of periplasmic enzymes by whole cells is reduced (termed "cryptic") are also found to show greatly reduced uptake of labeled adenosine 5'-monophosphate (5'-AMP), providing a rapid assay for crypticity. The crypticity of 3'- and 5'-nucleotidase has been examined as a function of substrate concentration. The Km for 3'- or 5'-AMP increases in the cryptic mutants when whole cells are used as the enzyme source. The Vmax is not altered. Electrophoretic analysis of protein prepared from cell envelopes showed that three cryptic mutants have a polypeptide absent from the outer membrane and a relatively high proportion of a polypeptide in the inner membrane. Analysis of the molar ratios of constituent sugars of the lipopolysaccharides showed no differences between three cryptic mutants and the parent strain. One cryptic mutant (3--41), however, has altered sensitivity to phage T4. By selection for phage resistance, derivatives of the cryptic mutants that are deoxycholate sensitive have been obtained. These mutants are no longer cryptic. We suggest that cryptic mutants have an altered outer membrane, with decreased permeability to 3'- and 5'-AMP, as a result of an altered polypeptide.